ANALYSIS OF PRICE FACTORS AND PRODUCT QUALITY ON PURCHASE DECISIONS THROUGH CONSUMER SATISFACTION OF MINROSE PRODUCTS IN TEACHING FACTORY PROCESSING DIVISION OF TEGALAMPEL 1 STATE VOCATIONAL SCHOOL OF BONDOWOSO VOCATIONAL SCHOOL - Marditasari, Mirza; Subagja, Hariadi; Kasutjianingati, Kasutjianingati (Jurnal Pertanian, 2019)
Rosela (Hibiscus sabdariffa L.) is used for drinks because it contains organic acids, polysaccharides, and flavonoids that are useful in preventing cancer, controlling blood pressure, promoting blood circulation, and promoting defecation, so it is feasible to be developed. Teaching Factory Tegalampel Bondowoso Processing Division of the PP Negeri 1 Vocational School captures the potential for the development of rosella by producing Minrose processed products, ready-to-drink and healthy packaging drinks from Rosela flowers as one of the superior products suitable for consumption for all people. Sales fluctuations assume that managers need to conduct studies by conducting price policies and building positive perceptions about product quality through customer satisfaction for purchasing decisions. Researchers used samples to consumers or buyers of Minrose products at the age of 15 to 60 as many as 70 people. This study uses path analysis analysis method that shows the results that the price affects consumer satisfaction (ρX1.Z = 0.387 with Sign. 0.001), product quality has an effect on customer satisfaction (ρX2.Z = 0.294 with Sign. 0.009), the price has no effect on purchasing decision (ρX1.Y = 0.046 with Sign. 0.630 and Indirect effect = 0.157 and Total Coefficient = 0.203), product quality affects purchasing decisions (ρX2.Y = 0.457 with Sign. 0,000 and Indirect effect = 0.117 and Total Coefficient = 0.576 ), consumer satisfaction affects the purchasing decision (ρZ.Y = 0.407 with Sign. 0,000) Minrose products at the Teaching Factory of the Processing Division of SMK PP Negeri 1 Tegalampel Bondowoso.